ANALYSIS OF WAYS TO STABILIZE THE QUALITY OF SOUR CREAM SECTION 1 - Рижкова, Таїсія; Лисенко, Ганна; Гейда, Ірина (SWorldJournal, 2024)
The article reports that the quality of sour cream is influenced by many factors, among which are the quality of the cream, the type of leaven, and compliance with the technological process during the processing of dairy raw materials into the above-menti